National Curriculum Education Policy "Curriculum Merdeka And Its Implementation" - Azmi, Chairul; Hadiyanto, Hadiyanto; Rusdinal, Rusdinal (International Journal of Educational Dynamics, 2023)
The Merdeka Curriculum is a curriculum introduced by the Ministry of Education, Culture, Research, and Technology in 2021 as an effort to improve the education system in Indonesia. In the era of globalization, the demands on students' abilities are not only limited to academic abilities, but also life skills abilities, creativity, and innovation. The Merdeka curriculum is designed to meet these demands and help students be prepared for future challenges. Improvement of the national curriculum Previously, the national curriculum in Indonesia has undergone several revisions and adjustments, but there are still shortcomings in terms of life skills development and innovation. Therefore, Curriculum Merdeka was created to enhance the previous national curriculum and provide a more holistic and relevant learning experience for students. This writing methodology uses the literature study methodology. The writing of this article is done by reviewing journals related to curriculum and implementation. The results of the study found that the character development of Curriculum Merdeka students also aims to develop superior student character, such as critical thinking skills, collaboration, and good ethics. That way, students not only become academically smart, but also able to become individuals who are more competitive and character. With this background, the Merdeka Curriculum is expected to provide a more meaningful and relevant learning experience for students in Indonesia.